2015
DOI: 10.3892/ol.2015.2927
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of benign struma ovarii, pseudo-Meigs’ syndrome and elevated serum CA 125: Case report and review of the literature

Abstract: Abstract. Struma ovarii is an uncommon ovarian teratoma comprised predominantly of mature thyroid tissue. The combination of pseudo-Meigs' syndrome, and elevation of CA 125 to the struma ovarii is a rare condition that can mimic ovarian malignancy. We reported a case of benign struma ovarii, presenting with the clinical features of advanced ovarian carcinoma: complex pelvic mass, gross ascites, bilateral pleural effusion and markedly elevated serum CA 125 levels. The patient underwent total abdominal hysterect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Even though CA-125 is increased in 80% of epithelial ovarian carcinomas, its specificity in the diagnosis is limited, as this marker may be elevated also in other malignancies (endometrium, breasts, lungs), as well as in endometriosis, or even in physiologic states like menstruation or pregnancy [ 9 , 26 ]. Reports have shown that CA-125 is not a specific tumor marker for MSO, an important percentage of cases having normal levels of CA-125 [ 9 11 , 26 ]. In a recent research performed on 144 published cases of MSO, only 51.6% had high levels of CA-125 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though CA-125 is increased in 80% of epithelial ovarian carcinomas, its specificity in the diagnosis is limited, as this marker may be elevated also in other malignancies (endometrium, breasts, lungs), as well as in endometriosis, or even in physiologic states like menstruation or pregnancy [ 9 , 26 ]. Reports have shown that CA-125 is not a specific tumor marker for MSO, an important percentage of cases having normal levels of CA-125 [ 9 11 , 26 ]. In a recent research performed on 144 published cases of MSO, only 51.6% had high levels of CA-125 [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pseudo-Meigs syndrome is a similar condition associated with pelvic tumors, except for the fact that these ovarian tumors are benign, such as primary ovarian malignancies, ovarian metastasis of gastrointestinal malignancies, uterine leiomyomas and so on. [3][4][5][6][7][8] Pseudo-Meigs syndrome due to uterine leiomyoma is very rare. Here we report a patient case of pseudo-Meigs syndrome caused by a giant uterine leiomyoma with cystic degeneration, which was initially suspected to be a case of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 A number of studies have reported cases of Pseudo-Meigs syndrome associated with struma ovarii, mature teratoma, uterine myoma, ovarian cancer and ovarian metastasis of malignancies. The Pseudo-Meigs syndrome is often diagnosed upon close examination and classically during follow-up appointments subsequently to the treatment of other malignanttumors [4][5][6][7][8]. The pathophysiology or the origin of the ascites and pleural effusion found in patients presenting either the Meigs or the pseudo-Meigs syndrome remains uncertain.…”
mentioning
confidence: 99%
“…3 Meigs' syndrome is the association of fibromas, ascites, and pleural effusion that resolve after surgical resection of the ovarian tumor. 3,4,11,12 Spiegelberg was the first to present the description of the syndrome in 1866; two decades later, Trait reported that the presence of an ovarian tumor with ascites and pleural effusion is not always associated with malignancy.…”
Section: -4mentioning
confidence: 99%
“…1,5,7,12,18,19 PMS associated with struma ovarii and accompanied by a rise in Ca125 is very rare: only eight cases have been reported in the medical literature to date (Table 1). [2][3][4]7,8,11,12,18,19 The possible causes of the increase of Ca125 in Meigs' syndrome include irritation of the mesothelial cells by the ovarian tumor, ascites, or pleural effusion, which leads to the antigen being released onto the surface of the serous membranes or the peritoneum. 7,16,18,19 To date, no correlation has been found among volume of ascites fluid volume, tumor size, or the value of Ca125 in Meigs' syndrome.…”
mentioning
confidence: 99%